Marketing analysis of snails in selected snail markets in Ibadan, Nigeria - Okeleke, S.O. (ADAN JOURNAL OF AGRICULTURE, 2024)
The study was carried out investigate marketing of snails in selected snail markets in Ibadan, Nigeria. Information was collected with the use of structured questionnaires and oral interview. Descriptive statistics such as frequency and percentage and regression were applied to analyze the socio-economic variables. For the regression analysis, linear function had F-ratio that was significant and highest co-efficient of multiple determination (R2) values of 0.971. The study revealed that more females (92.5%) than males (7.5%) were involved in snail marketing in the study area. Majority of the respondents (80.0%) were married while 46.2% were within age bracket of 50-59 years. The result further revealed that 82.5% sourced for capita through personal savings. Per annum profit of N 340,200.00/marketer indicates the profitability of sales. Marketing constraints facing the snail marketers in the study area are price fluctuation, inadequate credit facilities irregular supply and snail mortality. Enhancement of snail marketing can be through cooperative group formation to access credit facilities and good road network provision by government to convey product to market